Contests versus Norms: Implications of Contest-Based and Norm-Based Intervention Techniques - Bergquist, Magnus; Nilsson, Andreas; Hansla, André (Frontiers in Psychology, 2017)
Interventions using either contests or norms can promote environmental behavioral change. Yet research on the implications of contest-based and norm-based interventions is lacking. Based on Goal-framing theory, we suggest that a contest-based intervention frames a gain goal promoting intensive but instrumental behavioral engagement. In contrast, the norm-based intervention was expected to frame a normative goal activating normative obligations for targeted and non-targeted behavior and motivation to engage in pro-environmental behaviors in the future. In two studies participants (N = 347) were randomly assigned to either a contest- or a norm-based intervention technique. Participants in the contest showed more intensive engagement in both studies. Participants in the norm-based intervention tended to report higher intentions for future energy conservation (Study 1) and higher personal norms for non-targeted pro-environmental behaviors (Study 2).These findings suggest that contest-based intervention technique frames a gain goal, while norm-based intervention frames a normative goal.